RESEARCH OF STRESS-STRAIN STATE OF THE TRACK WITH CONNECTION OF CHECKPOINT - Umanov, M. I.; Kovalov, V. V.; Sova, S. M. (Science and Transport Progress, 2003)
The stresser-deformed estimation with the fastenings KПП. The comparison of these parameters with the analogous ones for a track with fastenings KБ have shown close enough conformity.